Growth regulators, sucrose and potassium in the growth and biochemical activity of Curcuma longa L. micropropagated - Ferrari, Meire Pereira de Souza; Queiroz, Mayara dos Santos; Andrade, Matheus Marquezini de; Trettel, Jéssica Rezende; Magalhães, Hélida Mara (Scientia Agraria Paranaensis, 2020)
Curcuma longa L. is a plant widely used for its pharmacological and medicinal properties, however, does not have a conclusive micropropagation protocol. The objective was to evaluate how growth regulators, sucrose and potassium influence the growth and biochemical activity of Curcuma longa seedlings grown in vitro. Shoots were inoculated in culture medium supplemented with 6-benzylaminpurine - BAP (8.88 and 17.76 μM), Kinetin - KIN (0.92 and 2.16 μM) and naphthalene acetic acid - NAA (2.16 and 7.20 μM), potassium iodide KI (25 and 50 μM) and sucrose (30 and 60 gL-1). Growth regulators at the lowest concentration and 30 gL-1 sucrose promoted increases in growth of C. longa. Antioxidant activity was high in all treatments. The activity of the enzymes catalase and ascorbato peroxidase were increased in the two treatments that contained the highest concentrations of growth regulators. It is concluded that the addition of growth regulators such as cytokinins and auxins are fundamental to increase the number of leaves and growth of shoots in C. longa. Since the best concentrations are in the range of 4.44 to 8.88 μM of (BAP) and 2.16 of NAA. The addition of supplemental potassium in the culture medium is not necessary, and the beneficial effects of doubling the usual sucrose concentration are nullified if other constituents of the medium are altered. The antioxidant activity and enzymes had their activity altered, especially in treatments that did not contain growth regulators.